PBPK Model of Morphine Incorporating Developmental Changes in Hepatic OCT1 and UGT2B7 Proteins to Explain the Variability in Clearances in Neonates and Small Infants. (19th June 2018) - Emoto, Chie; Johnson, Trevor N.; Neuhoff, Sibylle; Hahn, David; Vinks, Alexander A.; Fukuda, Tsuyoshi
Abstract : Morphine has large pharmacokinetic variability, which is further complicated by developmental changes in neonates and small infants. The impacts of organic cation transporter 1 (OCT1) genotype and changes in blood‐flow on morphine clearance (CL) were previously demonstrated in children, whereas changes in UDP‐glucuronosyltransferase 2B7 (UGT2B7) activity showed a small effect. This study, targeting neonates and small infants, was designed to assess the influence of developmental changes in OCT1 and UGT2B7 protein expression and modified blood‐flow on morphine CL using physiologically based pharmacokinetic (PBPK) modeling. The implementation of these three age‐dependent factors into the pediatric system platform resulted in reasonable prediction for an age‐dependent increase in morphine CL in these populations. Sensitivity of morphine CL to changes in cardiac output increased with age up to 3 years, whereas sensitivity to changes in UGT2B7 activity decreased. This study suggests that morphine exhibits age‐dependent extraction, likely due to the developmental increase in OCT1 and UGT2B7 protein expression/activity and hepatic blood‐flow.